Analisis pemanfaatan aplikasi online pada pembelajaran daring (dalam jaringan) di sekolah dasar - Dewi, Metha Asmara; Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2021)
During the Covid-19 pandemic, all levels of education in Indonesia carried outlearning activities from home which were carried out through online learning and continued until the situation was declared better. The purpose of this study was to obtain planning implementation, and evaluation of the using of online applications in online learning (online) at SDN Mangkubumen Lor No 15. The research method used was descriptive qualitative with a case study approach. The research subjects were teachers and students in high class. The data collection technique was carried out by interviews, questionnaires and document analysis with data validity testing using technical triangulation and source triangulation. Data analysis used interactive techniques Miles & Huberman. The results showed that: (1) online learning to planhas made use of the online application and its features according to the needs, making lesson plans and preparing teaching materials; (2) the implementation of online learning was used for providing materials and assignments through online applications, (3) evaluating online learning was difficult for giving reflection to students. Therefore, teachers and students needed to develop a more varied use of online applications so that online learning can be carried out better.